2013
DOI: 10.1007/s00270-013-0696-x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Assisted Thrombolysis in Submassive and Massive Pulmonary Embolism: Assessment of Lung Obstruction Before and After Catheter-Directed Therapy

Abstract: UA thrombolysis is promising in massive and submassive PE treatment and shows safe results. Patients showed improved thrombus burden, and rapid improvement in right cardiac function, whereas minimizing bleeding risk and ICU time were minimized. This results of this study provide the foundation for future comparative studies in treatment of large PEs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…compared favorably with the CDT group, in which only 50% of the patients had complete thrombus removal with a significantly longer thrombolytic infusion time of 26.7 hours and a hemorrhagic complication rate of 21.4%. Quintana et al (20) reported using tPA with USAT in 10 patients with acute massive or submassive PE. The median tPA dose and infusion time in their cohort was 18 mg (range, 7-38 mg) and 20.8 hours (range, 12-49 h), respectively.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…compared favorably with the CDT group, in which only 50% of the patients had complete thrombus removal with a significantly longer thrombolytic infusion time of 26.7 hours and a hemorrhagic complication rate of 21.4%. Quintana et al (20) reported using tPA with USAT in 10 patients with acute massive or submassive PE. The median tPA dose and infusion time in their cohort was 18 mg (range, 7-38 mg) and 20.8 hours (range, 12-49 h), respectively.…”
Section: Resultsmentioning
confidence: 98%
“…The median tPA dose and infusion time in their cohort was 18 mg (range, 7-38 mg) and 20.8 hours (range, 12-49 h), respectively. Cessation of thrombolysis in these three studies was determined by the adequacy of thrombus removal on repeat pulmonary angiography (18,19) or repeat CT angiography (20).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies used a fixed dose of rt-PA (10mg over 15 hours) per treated lung, while other used pulse infusion or slow infusion [ 12 , 18 , 23 ]. Treatment duration also varied among studies and outcome is guided by clinical or angiographic measures [ 11 , 24 - 26 ].…”
Section: Reviewmentioning
confidence: 99%